2018
DOI: 10.1097/gox.0000000000001893
|View full text |Cite
|
Sign up to set email alerts
|

Current Challenges of Plastic Surgical Care in Sub-Saharan Africa (Maputo, Mozambique)

Abstract: Background:Limited data exist on plastic surgery practices in Sub-Saharan Africa. The aim of this study was to characterize the spectrum of disease and operative procedures at a teaching hospital in Maputo, Mozambique to help understand the challenges of providing care for the local providers and to provide contextual relevance for training through partnerships.Methods:A mixed-methods approach was utilized to perform an ongoing needs assessment. A retrospective review was performed of plastic surgery operative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 13 publications
0
13
2
Order By: Relevance
“…However, this fact began to direction of this surgery, as the concept of plastic surgery in this region is still largely considered a cosmetic luxury. The total number of patients reviewed in this study is the same as that available in international data [1,7,8]. A study done by Kieran et al showed the ratio of elective to emergency procedures to be 2:1 [13], whereas in our series the emergency operations were almost equal to elective ones.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, this fact began to direction of this surgery, as the concept of plastic surgery in this region is still largely considered a cosmetic luxury. The total number of patients reviewed in this study is the same as that available in international data [1,7,8]. A study done by Kieran et al showed the ratio of elective to emergency procedures to be 2:1 [13], whereas in our series the emergency operations were almost equal to elective ones.…”
Section: Discussionmentioning
confidence: 66%
“…In contrast, some developing countries consider plastic surgery as an unnecessary field, and the establishment of a department in publicly funded hospitals was not considered [7]. For instance, there is a significant lack of data from sub-Saharan Africa regarding plastic surgery practice [8]. However, plastic surgery cases represent about 20% of the surgical workload in rural hospitals [9].…”
Section: Introductionmentioning
confidence: 99%
“…There is limited access to safe surgical care in many LMICs [ 2 , 31 , 32 ]. Past work has cited burn depth to be the most important indication for surgery, but this work suggests the additional importance of joint involvement to the treatment paradigm [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In many developing countries interventions are primarily required for reconstructive needs in trauma, burns, and congenital anomalies. [10][11][12][13][14][15] The spectrum of reconstructive surgery procedures is widening with the top five surgeries at our center being trauma reconstruction, skin tumor surgeries, hand surgeries, AV fistula creation, and oculoplasty, similar to American Society of Plastic Surgery (ASPS) 2018 statistics, 16 where tumor removal, laceration repair, maxillofacial surgery, scar revision, and hand surgery topped the charts. But there are variations.…”
Section: Discussionmentioning
confidence: 99%
“…In many developing countries interventions are primarily required for reconstructive needs in trauma, burns, and congenital anomalies. 10 11 12 13 14 15 …”
Section: Discussionmentioning
confidence: 99%